FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN SISWA BERSEKOLAH DI SMK BINA PROFESI PEKANBARU - Bambang (P3M STKIP 'Aisyiyah Riau, 2014)
ABSTRACT This research was conducted in Pekanbaru City with the aim of knowing: The Influence of Decision Factors of Students Attending Pekanbaru's Professional Vocational School. This study seeks to dig up information about the influence of factors of school students in influencing the decision of the Pekanbaru Bina Profession Vocational School in Pekanbaru. A sample of 54 students. The variables that are the focus of this study are social status, facilities and infrastructure, religious values, school achievement as the dependent variable (X) and school decisions as an independent variable (Y). Data analysis method used is quantitative descriptive analysis with the help of SPSS 21. tools for windows. The results of research on factors of social status, facilities and infrastructure, religious values, and school achievement in influencing the decision of students to attend vocational high school in Pekanbaru concluded that partially independent social status variables (X1) obtained a tcount of 2.319, facilities and infrastructure (X2) Tcount value is 2,816, religious value (X3) Tcount value is 2,239, and school achievement (X4) Tcount value is 2,722, addressing the positive value the better the five variables will be better also in influencing the decision of attending school at SMK Bina Pekanbaru profession, continued with the analysis of variables simultaneously / together the analysis of the regression coefficients of the five variables is significant.